PERGESERAN NILAI NASIONALISME DALAM NOVEL NAGABONAR JADI 2 KARYA AKMAL NASERY BASRAL - Siti Ulfiyani (Sasindo : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2013)
This research entitled ?óÔé¼?ôThe Shifting of Nationalism Value in Novel Nagabonar Jadi 2 by Akmal Nasery Basral?óÔé¼?Ø. The problem of this research is How does the shifting of nationalism in Novel Nagabonar Jadi 2 bu Akmal Nasery Basral? The aim of this research is to describe the shifting of nationalism in Novel Nagabonar Jadi 2 bu Akmal Nasery Basral. The methods ?é?áused?é?á to analyze the problem is qualitative descriptive analysis. The source of the research data comes from Novel Nagabonar Jadi 2 by Akmal Nasery Basral and some books which relevan with the research object. The shifting of nasionalism value that analyzed divided into two explanations, they are nationalism on the narrow meaning and nationalism on the broad meaning. Nationalism on the narrow meaning in the novel can be seen from the way Nagabonar, as the main character, looking the relation between Indonesia and another nation in the world, especially Japan and Ducth. Nagabonar ?é?áalso has a skeptical attitude toward Indonesian people that reputed as the figure regardless ?é?ápatriot?é?á defending nation. Based on the first analysis, Nagabonar argued Indonesia is not supposed to cooperate with the ex-colonizer that has made them suffered. That Nagabonar act showed the sceptical of nationalism in his soul. After experiencing some incidents, Nagabonar has changed his mind. He starts to open his mind?é?á and?é?á relized that Indonesia has been independent and is developing which need help from other contries to realize. Key words:Kata kunci :pergeseran, nilai, nasionalisme